On the sol-gel synthesis and characterization of (BaSr)(CeZr)O-3-based fuel cell electrolytes - Jaiswal, Shivendra Kumar; Choi, Sung Min; Hong, Jongsup; Yoon, Kyung Joong; Son, Ji-Won; Kim, Byung-Kook; Lee, Hae-Weon; Lee, Jong-Ho (SPRINGER HEIDELBERG, 2016)
Proton-conducting ceramics have been very useful due to their potential applications in fuel cells, electrolysers, and hydrogen membranes. The proton-conducting fuel cell electrolytes (Ba1-x Sr (x) )(Ce0.75Zr0.10Y0.15)O3-delta (x = 0-1.0) have been synthesized through sol-gel method and characterized with regard to phase, structural stability, and electrical conductivity. The structural behavior has been investigated by X-ray diffraction and theRaman spectroscopy. The XRD analysis shows perovskite-type cubic structure and values of lattice parameter lie in the range of similar to 4.29 to similar to 4.40 . Strontium substitution leads to lattice contraction, strengthening of the metal-oxygen bond, and increase of oxygen content (3-delta). The Raman spectra show different types of stretching/vibrations corresponding to octahedral, M-O stretching, and oxygen vacancies. The electrical conduction was found to be protonic in nature and decreases with increase of strontium insertion. The composition x = 0.4 shows relatively better structural stability against humid air/boiling water condition while inferior in carbon dioxide atmosphere.
Keywords: DOPED BARIUM ZIRCONATE; CHEMICAL-STABILITY; PROTON CONDUCTOR; OPTICAL-ABSORPTION; PHASE; NONSTOICHIOMETRY; TRANSPORT; MEMBRANE; BEHAVIOR; GD